Foreclosures, House Prices, and the Real Economy - MIAN, ATIF; SUFI, AMIR; TREBBI, FRANCESCO (Journal of Finance, 2015)
ABSTRACT From 2007 to 2009, states without a judicial requirement for foreclosures were twice as likely to foreclose on delinquent homeowners. Analysis of borders of states with differing foreclosure laws reveals a discrete jump in foreclosure propensity as one enters nonjudicial states. Using state judicial requirement as an instrument for foreclosures, we show that foreclosures led to a large decline in house prices, residential investment, and consumer demand from 2007 to 2009. As foreclosures subsided from 2011 to 2013, the foreclosure rates in nonjudicial and judicial requirement states converged and we find some evidence of a stronger recovery in nonjudicial states.